Unsealing method for commercial plastic package device containing Cu lead

Through the electrolytic corrosion method combined with the acid corrosion method, the problem of difficult to efficiently etch Cu lead plastic sealing devices in the prior art is solved, and the standardized etching process is realized, and the original state of Cu leads and Al pads is retained.

CN119786382APending Publication Date: 2025-04-08Shanghai Institute of Basic Aerospace Technology
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411850769.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The prior art cannot efficiently etch commercial plastic sealing devices containing Cu leads under standardization requirements, and traditional methods are prone to damage Cu leads and Al pads during the etching process.

Method used

X-rays were used to determine the highest point of Cu lead and the distribution area of ​​the bonding point, combined with laser ablation method and acid corrosion method, the epoxy resin was decomposed through electrolytic corrosion method and ceramic filler was retained, and the Cu lead and bonding area were gradually exposed.

Benefits of technology

It is realized that the plastic-encapsulated device is efficiently etched without damaging the Cu leads and Al pads, which shortens the etching time and improves the etching accuracy and reliability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119786382A_ABST
    Figure CN119786382A_ABST
Patent Text Reader

Abstract

The invention discloses an unsealing method for a commercial plastic package device containing a Cu lead. The unsealing method specifically comprises the following steps: determining the highest position of the Cu lead of the plastic package device and a bonding point distribution area by adopting X rays; grooving the positioning window area of the plastic package material on the upper surface of the device by adopting a laser ablation method; controlling the thickness of the molding compound above the highest part of the Cu lead within a proper range by combining X rays; performing electrolytic corrosion on the plastic package material at the bottom of the slotted window area by adopting a mixed solution of fuming nitric acid and concentrated sulfuric acid, decomposing the epoxy resin, and retaining the ceramic filler; dissolving the residual mixed solution of fuming nitric acid and concentrated sulfuric acid with acetone; removing the ceramic filler by using deionized water; isopropanol is adopted to keep the device dry; and an SEM scanning electron microscope is adopted to judge the reliability of the Cu lead and the Cu lead / Al bonding pad after electrolytic corrosion. According to the invention, the corrosion to the plastic package material is accelerated, and the problem that the commercial plastic package device containing the Cu lead cannot be efficiently etched under the standard requirement in the prior art is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a reliability analysis technology in the field of commercial devices, and in particular to a method for unsealing a commercial plastic-sealed device containing a Cu lead. Background Art

[0002] Cu leads are widely used in commercial plastic-encapsulated devices due to their low cost, high thermal conductivity, and high electrical conductivity, becoming a new generation of commercial low-cost materials to replace Au leads. Compared with Au leads, the high electrical conductivity of Cu leads enables them to carry higher currents at the same diameter, which is conducive to further miniaturization of plastic-encapsulated devices.

[0003] However, the atomic structure and physical properties of Cu make it easy to form Cu-Al intermetallic compounds with Al pads. Due to the poor sealing of plastic-encapsulated devices, water vapor and chloride ions can easily pass through the gap between the plastic-encapsulated shell and the lead frame, and directly contact the internal Cu lead bonding area, causing the Cu-Al intermetallic compounds to be corroded. In addition, the thermal expansion coefficients of the Cu lead and the plastic encapsulation material are quite different, which may cause cracks at the necking of the Cu lead and the interface of the Cu lead / Al pad due to thermal expansion and contraction. In order to evaluate the electrical and mechanical connection reliability of the Cu lead and the Cu lead / Al pad bonding area, a standardized plastic-encapsulated device unsealing process needs to be developed. The problem that needs to be solved urgently is how to expose the Cu lead, ball bonding, and wedge bonding areas as much as possible without affecting the original state of the Cu lead and introducing new defects, so as to subsequently evaluate the reliability of the Cu lead bonding of different devices.

[0004] Currently, there are several methods for desealing Cu leads: laser ablation, plasma etching, and acid etching.

[0005] (1) Laser ablation is a method of applying a high-power laser beam to the surface of the plastic packaging material, causing the plastic packaging material to absorb the laser energy and evaporate under the action of near-infrared light, and finally transform into plasma. However, if the laser ablation method acts directly on the Cu lead, it will greatly affect the reliability of the Cu lead.

[0006] (2) Plasma etching can effectively etch the plastic packaging material by mixing O2 gas and CF4 gas to form a plasma mixed gas. However, compared with the acid etching method, the plasma etching rate is relatively slow.

[0007] (3) The acid etching method is to corrode the plastic encapsulation material through fuming nitric acid HNO3 or concentrated sulfuric acid H2SO4. If only fuming nitric acid is used as the etching liquid, the Cu lead will react with the fuming nitric acid to generate Cu(NO3)2, forming pits in the lead bonding area; if only concentrated sulfuric acid is used as the etching liquid, the Al pad will react with the concentrated sulfuric acid to generate Al2(SO4)3, which will continuously corrode the Al pad coating and eventually cause the Cu lead ball bond to fall off. Therefore, it is necessary to select a suitable ratio of fuming nitric acid and concentrated sulfuric acid to avoid damage to the Cu lead and Al pad. In addition, although the speed at which fuming nitric acid or concentrated sulfuric acid corrodes the plastic encapsulation material is faster than the plasma etching method, it is still relatively slow compared to the laser ablation method.

[0008] In summary, the traditional laser ablation method, plasma etching method, and acid etching method all have their own advantages and disadvantages. Under the premise of not damaging the Cu lead and Al pad, using any of the above methods alone cannot efficiently etch the plastic encapsulation material, and the bonding conditions of the Cu lead after each etching are different. Therefore, it is necessary to develop a reliable and efficient method for unsealing commercial plastic encapsulated devices containing Cu leads to solve the problem of efficiently etching commercial plastic encapsulated devices containing Cu leads under standardized requirements. Summary of the invention

[0009] The purpose of the present invention is to provide a method for unsealing a commercial plastic-sealed device containing Cu leads, so as to solve the problem that the prior art cannot efficiently etch the commercial plastic-sealed device containing Cu leads under standardized requirements.

[0010] In order to achieve the above-mentioned object, the present invention provides a method for unsealing a commercial plastic-sealed device containing Cu leads, the method specifically comprising:

[0011] S1, using X-ray to determine the highest point of the Cu lead and the distribution area of ​​the bonding points of the plastic packaged device;

[0012] S2, using laser ablation to groove the positioning window area of ​​the plastic packaging material on the upper surface of the device, and combining X-ray to control the thickness of the plastic packaging material above the highest point of the Cu lead within an appropriate range;

[0013] S3, using a mixture of fuming nitric acid and concentrated sulfuric acid to electrolytically corrode the plastic sealing material at the bottom of the slotted window area, decompose the epoxy resin, and retain the ceramic filler;

[0014] S4, using acetone to dissolve the residual fuming nitric acid and concentrated sulfuric acid mixture; using deionized water to remove the ceramic filler; using isopropyl alcohol to keep the device dry;

[0015] S5, using scanning electron microscope (SEM) to determine the reliability of Cu lead and Cu lead / Al pad after electrolytic corrosion.

[0016] Further, the use of X-rays in step S1 to determine the highest point of the Cu lead of the plastic-encapsulated device is to determine the device pad plating material, Cu lead size, and device plastic encapsulation material thickness according to the product manual, and to observe the device from the front using X-rays to determine the highest point of the Cu lead of the device;

[0017] Furthermore, the bonding point distribution area of ​​the plastic-encapsulated component is determined in step S1 by observing the component from the top surface using X-rays to determine the bonding point distribution area of ​​the component.

[0018] Furthermore, the method of using laser ablation to groove the positioning window area of ​​the plastic packaging material on the upper surface of the device in step S2 is as follows:

[0019] A1. Use solder to short-circuit all external pins of the plastic-encapsulated device to provide circuit bias conditions for the device;

[0020] A2. Determine the optimal size and shape area for laser etching based on the highest point of the Cu lead and the distribution area of ​​the bonding points observed by X-ray, and use it as the plastic sealing slot window area;

[0021] A3. Use a positioning tool of a laser etching machine to mark the plastic sealing slot window area, and limit the area for subsequent plastic sealing opening to the slot window area.

[0022] Furthermore, in step S2, the thickness of the plastic encapsulation material above the highest point of the Cu lead is controlled within an appropriate range in combination with X-rays, and the plastic encapsulation device after laser etching is further observed from the front by X-rays to ensure that the distance between the lowest point of the window area after laser etching and the highest point of the Cu lead is less than or equal to 1 mm.

[0023] Furthermore, in step S3, the plastic sealing material at the bottom of the slotted window area is electrolytically corroded by using a mixture of fuming nitric acid and concentrated sulfuric acid to decompose the epoxy resin and retain the ceramic filler. The specific method is as follows:

[0024] B1, using antistatic tape that does not react with the fuming nitric acid and concentrated sulfuric acid mixture to cover the area outside the slot, 90-98% fuming nitric acid HNO3 and 90-98% concentrated sulfuric acid H2SO4 are mixed in a mass ratio of 4:1-2:1 to form the fuming nitric acid and concentrated sulfuric acid mixture, and the temperature of the fuming nitric acid and concentrated sulfuric acid mixture is maintained at 50-80°C to generate NO2 + Ions and HSO4 - ion;

[0025] B2. Connect the short-circuited external pin of the device to the positive pole of the power supply. When the power is on, hydrogen H2 is formed on the surface of the metal sheet corresponding to the negative pole of the power supply. -The ions begin to electrolytically corrode the epoxy resin in the plastic packaging material, and the plastic packaging device connected to the positive electrode of the power supply and the negative electrode metal sheet are immersed in the fuming nitric acid and concentrated sulfuric acid mixture at the same time. + The ions continuously decompose the epoxy resin; the remaining main parts of SiO2, Al2O3, and AlN ceramic fillers in the plastic packaging material float in the mixed liquid and adhere to the chip surface, pad surface, and wire bonding; HSO4 - The ions are adsorbed on the Cu lead;

[0026] B3. Maintain the power supply voltage of the electrolytic corrosion at 16 V, and take out the plastic-encapsulated device from the fuming nitric acid and concentrated sulfuric acid mixture every 30 seconds; check the electrolytic corrosion degree of the epoxy resin and the visibility of the Cu wire bonding by a low-power optical microscope. When the Cu wire bonding is clearly visible, use a high-power optical microscope to preliminarily measure the Cu lead diameter and the potential pit area on the Cu lead surface.

[0027] Furthermore, in step S4, acetone is used to dissolve the residual fuming nitric acid and concentrated sulfuric acid mixture, and the specific method is as follows:

[0028] The device is rinsed with acetone to dissolve and remove the residual fuming nitric acid and concentrated sulfuric acid mixture on the surface of the device.

[0029] Furthermore, the ceramic filler is removed by using deionized water in step S4, and the specific method is as follows:

[0030] Gently spray deionized water on the surface of the Cu lead to remove HSO4 on the surface of the Cu lead. - Ion protective coating, as well as SiO2, Al2O3, and AlN ceramic fillers remaining after reaction in the plastic packaging material.

[0031] Furthermore, the specific method of using isopropyl alcohol to keep the device dry in step S4 is as follows:

[0032] Rinse the device with isopropyl alcohol to remove any residual deionized water on the device surface and keep the device surface dry.

[0033] Furthermore, the reliability of the Cu lead and the Cu lead / Al pad after electrolytic corrosion is determined by using a SEM scanning electron microscope in step S4, and the specific method is as follows:

[0034] After the electrolytic corrosion is completed, the SEM scanning electron microscope is used to further observe the device after unsealing and drying to determine whether the ball bonding and wedge bonding are completely visible, measure the diameter of the Cu lead, and compare it with the product manual; when the reliability of the Cu lead and Cu lead / Al pad is good, remove the anti-static tape covering the area outside the window slot of the plastic-encapsulated device.

[0035] Compared with the prior art, the beneficial effects of the present invention include:

[0036] (1) The present invention uses a combined method of X-ray and laser ablation to thin the plastic encapsulation material on the surface of the Cu lead to less than 1 mm, effectively shortening the volume of the plastic encapsulation material to be removed later.

[0037] (2) The laser ablation method used in the present invention does not directly act on the surface of the Cu lead, and effectively preserves the original state of the Cu lead.

[0038] (3) The present invention adopts a combined method of acid corrosion and electrolytic corrosion, which can accelerate the corrosion of the plastic packaging material. The corrosion speed is faster than that of pure acid solution, and the corrosion process can be controlled more accurately.

[0039] (4) The present invention adopts a combined method of acid corrosion and electrolytic corrosion based on the laser ablation method, taking into account the influence of the mixed solution of fuming nitric acid HNO3 and concentrated sulfuric acid H2SO4 on the bonding strength of the Cu lead / Al pad during the accelerated corrosion process, thereby reducing the possibility of introducing corrosion defects on the surface of the Cu lead during the electrolytic corrosion process, making the electrolytic corrosion process more gentle, and not causing severe impact on the Cu lead / Al pad, thereby preserving the original state of the Cu lead / Al pad bonding to a large extent. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] The method for unsealing a commercial plastic-sealed device containing Cu leads of the present invention is provided by the following embodiments and drawings.

[0041] Figure 1 The present invention provides a schematic flow chart of a method for unsealing a commercial plastic-sealed device containing Cu leads.

[0042] Figure 2 This is a front X-ray schematic diagram of the plastic-encapsulated device provided by the present invention.

[0043] Figure 3 This is a schematic X-ray diagram of the top surface of the plastic-encapsulated device provided by the present invention.

[0044] Figure 4 This is a schematic diagram of short-circuiting all external pins of the plastic-encapsulated device provided by the present invention.

[0045] Figure 5 This is a top view of the laser-etched window area of ​​the plastic package device provided by the present invention.

[0046] Figure 6 This is a cross-sectional view of the laser-etched slotted window area of ​​the plastic package device provided by the present invention.

[0047] Figure 7 This is a schematic diagram of the electrolytic corrosion of the plastic-encapsulated device provided by the present invention.

[0048] Figure 8The cross section of the molding compound in the common commercially available molding device provided by the present invention.

[0049] In the figure: 111 is the plastic sealing slot window area, 112 is the lowest point of the window area, 113 is the highest point of the Cu lead, 114 is the metal sheet corresponding to the negative pole of the power supply, 115 is the external pin of the device, 116 is a mixture of fuming nitric acid and concentrated sulfuric acid, 117 is epoxy resin, and 118 is SiO2, Al2O3, and AlN ceramic fillers. DETAILED DESCRIPTION

[0050] The following is a further detailed description of a method for unsealing a commercial plastic-sealed device containing Cu leads according to the present invention in conjunction with the accompanying drawings.

[0051] The invention solves the problem that the prior art cannot efficiently etch a commercial plastic-sealed device containing a Cu lead under standardized requirements: X-rays are used to determine the highest point of the Cu lead and the distribution area of ​​the bonding points of the plastic-sealed device; a laser ablation method is used to groove a positioning window area of ​​a plastic-sealed material on the upper surface of the device; the thickness of the plastic-sealed material above the highest point of the Cu lead is controlled within a suitable range in combination with the X-ray; a mixed solution of fuming nitric acid and concentrated sulfuric acid is used to electrolytically corrode the plastic-sealed material at the bottom of the grooved window area to decompose the epoxy resin and retain the ceramic filler; acetone is used to dissolve the residual mixed solution of fuming nitric acid and concentrated sulfuric acid; deionized water is used to remove the ceramic filler; isopropyl alcohol is used to keep the device dry; and a SEM scanning electron microscope is used to determine the reliability of the Cu lead and the Cu lead / Al pad after electrolytic corrosion.

[0052] The present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments.

[0053] The schematic diagram of the process of unsealing a commercial plastic-sealed device containing Cu leads according to a preferred embodiment of the present invention is as follows: Figure 1 As shown, the method for unsealing a commercial plastic-sealed device containing Cu leads according to an embodiment of the present invention comprises the following steps:

[0054] S1, use X-ray to determine the highest Cu lead position and bonding point distribution area of ​​the plastic packaged device:

[0055] S11, determine the device pad plating material, Cu lead size, and device plastic packaging material thickness according to the product manual;

[0056] S12, such as Figure 2 As shown, the device is observed from the front using X-rays to determine the position of the highest Cu lead of the device;

[0057] S13, such as Figure 3 As shown, X-rays are used to observe the device from the top surface to determine the distribution area of ​​the device bonding points.

[0058] S2, laser ablation is used to groove the positioning window area of ​​the plastic encapsulation material on the upper surface of the device, and combined with X-rays, the thickness of the plastic encapsulation material above the highest point of the Cu lead is controlled within an appropriate range:

[0059] S21, such as Figure 4 As shown, all external pins of the plastic packaged device are short-circuited by solder to provide circuit bias conditions for the device;

[0060] S22, such as Figure 5 As shown, according to the highest Cu lead position and bonding point distribution area of ​​the device observed by X-ray in step S1, the optimal size and shape area range of laser etching is determined, and it is used as the plastic packaging slot window area 111; the positioning tool of the laser etching machine is used to mark the slot window area, and the area for subsequent plastic packaging unsealing is limited to the slot window area;

[0061] S23, such as Figure 5 As shown, according to the thickness of the plastic encapsulation material in the device product manual in step S1 and the position of the Cu lead of the device observed by X-ray, a laser etching machine is used to remove the plastic encapsulation material in the plastic encapsulation slot window area 111 as much as possible without damaging the Cu lead bonding area;

[0062] S24, such as Figure 6 As shown, the plastic package device after laser etching is observed from the front by X-ray to ensure that the distance between the lowest point 112 of the window area after laser etching and the highest point 113 of the Cu lead is less than or equal to 1 mm. If the distance is still greater than 1 mm, repeat step S23 until the distance is less than or equal to 1 mm.

[0063] S3, using a mixture of fuming nitric acid and concentrated sulfuric acid to electrolytically corrode the plastic sealant at the bottom of the slotted window area, decompose the epoxy resin, and retain the ceramic filler:

[0064] S31, using an antistatic tape that does not react with the fuming nitric acid and concentrated sulfuric acid mixture to cover the area outside the window slot of the plastic-encapsulated device, exposing only the slot window area, to prevent the plastic encapsulation material and external pins in the area outside the window slot from being corroded during the subsequent electrolytic corrosion process;

[0065] S32, such as Figure 7 As shown, 90-98% fuming nitric acid HNO3 and 90-98% concentrated sulfuric acid H2SO4 are mixed into a mixed solution in a mass ratio of 4:1-2:1, and the temperature of the fuming nitric acid and concentrated sulfuric acid mixed solution 116 is maintained at 50-80° C. to prevent the Cu lead and the Al pad from being corroded, and effectively electrolytically corrode the epoxy resin in the plastic sealing material;

[0066] If only fuming nitric acid HNO3 is used as the etching solution, the Cu lead will react with the fuming nitric acid HNO3 to generate Cu(NO3)2, forming pits on the surface of the Cu lead;

[0067] If only concentrated sulfuric acid H2SO4 is used as the etching solution, the Al pad will react with the concentrated sulfuric acid H2SO4 to generate Al2(SO4)3, which will continuously corrode the Al pad coating and eventually cause the Cu lead ball bonding to fall off;

[0068] 90-98% fuming nitric acid HNO3 and 90-98% concentrated sulfuric acid H2SO4 are mixed in a mass ratio of 4:1-2:1 to form a mixed solution. The mixed solution 116 will undergo a nitration reaction to produce NO2 + Ions and HSO4 - Ions prevent the Cu lead from reacting with fuming nitric acid HNO3, and also prevent the Al pad from reacting with concentrated sulfuric acid H2SO4;

[0069] S33, such as Figure 7 As shown, the short-circuited device external pin 115 is connected to the positive electrode of the power supply, and the device does not need to be in direct contact with the negative electrode of the power supply. On the surface of the metal sheet 114 corresponding to the negative electrode of the power supply, the positively charged H + The ions will acquire negative ions and form hydrogen H2. Negatively charged HSO4 - The ions will be adsorbed on the positively charged outer lead surface 115 of the plastic package component and the plastic package slot window area 111, and begin to electrolytically corrode the epoxy resin in the plastic package material;

[0070] S34, such as Figure 7 As shown, the plastic-encapsulated device connected to the positive electrode of the power source and the negative electrode metal sheet 114 are simultaneously immersed in the fuming nitric acid and concentrated sulfuric acid mixed solution 116 in a mass ratio of 4:1 to 2:1;

[0071] The plastic encapsulation material is mainly composed of epoxy resin (10-30% by mass), SiO2, Al2O3, AlN ceramic fillers (60-80% by mass), and curing agent (5-10% by mass). Among them, the mass ratio of the curing agent to the epoxy resin and SiO2, Al2O3, AlN ceramic fillers can be ignored;

[0072] like Figure 8 As shown, the gray area is mainly SiO2, Al2O3, and AlN ceramic fillers 118, while the white area is mainly epoxy resin 117;

[0073] like Figure 8 As shown, the NO generated by the nitration reaction of the fuming nitric acid and concentrated sulfuric acid mixture 116 is 2+The ions can replace the H hydrogen atoms on the benzene rings in the epoxy resin 117, destroying the repeating structure of the main chain of the epoxy resin 117, and generating trinitrophenol, which continuously decomposes the epoxy resin 117. As the epoxy resin 117 continuously decomposes, the remaining main parts of SiO2, Al2O3, and AlN ceramic fillers 118 in the plastic packaging material will remain, floating in the fuming nitric acid and concentrated sulfuric acid mixture 116, or bonded to the chip surface, pad surface, and between wire bonds;

[0074] Negatively charged HSO4 - The ions will be adsorbed on the positively charged Cu lead. HSO4 - The ions will form a protective coating on the Cu lead, NO2 + The ion corrosion on the Cu lead is negligible;

[0075] S35, maintaining the power supply voltage of electrolytic corrosion at 16V can accelerate the decomposition of epoxy resin 117 and prevent the Cu lead from melting due to excessive current passing through the Cu lead. Since the power supply voltage is applied to the interconnected external pins, each Cu lead of the device is a parallel circuit, and the voltage on each Cu lead is maintained at 16V, and the current passing through each Cu lead can be significantly reduced. For a Cu lead with a diameter of 20μm, the fusing current must reach more than 1A, which is much higher than the current limit value passing through each Cu lead below 16V;

[0076] S36, every 30 seconds, the plastic packaged device is taken out from the fuming nitric acid and concentrated sulfuric acid mixture 116, and the electrolytic corrosion degree of the epoxy resin 117 and the visibility of the Cu lead bonding are checked by a low-power optical microscope to avoid the fuming nitric acid and concentrated sulfuric acid mixture 116 passing through the HSO4 when the electrolytic corrosion time is too long. - Ion protective coating penetrates into the surface of Cu lead;

[0077] S37, when the Cu wire bonding is clearly visible, a high-power optical microscope is used to preliminarily measure the Cu wire diameter and the potential pit area on the Cu wire surface;

[0078] When the measured Cu lead diameter is the same as the Cu lead diameter specified in the device product manual, and the potential pit area on the Cu lead surface is negligible, the electrolytic corrosion process is terminated; generally, the fuming nitric acid and concentrated sulfuric acid mixed solution 116 in a mass ratio of 4:1 to 2:1 at a power supply voltage of 16V and a temperature of 50 to 80°C is the best experimental condition for electrolytic corrosion of epoxy resin-based plastic-encapsulated devices containing Cu leads, which can effectively remove the epoxy resin 117 and ensure that the corrosion of the Cu lead is minimal;

[0079] When the actually measured Cu lead diameter is significantly smaller than the Cu lead diameter specified in the device product manual, or the potential pit area on the Cu lead surface is larger, in the next sample device, the electrolytic corrosion time, or the power supply voltage, or the temperature of the fuming nitric acid and concentrated sulfuric acid mixture 116 is gradually reduced by 10% until the actually measured Cu lead diameter is the same as the Cu lead diameter specified in the device product manual and the potential pit area on the Cu lead surface is negligible, and then the electrolytic corrosion process is terminated.

[0080] S4, using acetone to dissolve the residual fuming nitric acid and concentrated sulfuric acid mixture 116, using deionized water to remove SiO2, Al2O3, AlN ceramic fillers 118, and using isopropanol to keep the device dry:

[0081] S41, washing the device with acetone to dissolve and remove the fuming nitric acid and concentrated sulfuric acid mixture 116 remaining on the surface of the device;

[0082] S42, gently spray deionized water on the surface of the Cu lead to remove HSO4 on the surface of the Cu lead. - SiO2, Al2O3, and AlN ceramic fillers 118 remaining after reaction in ion protection coating and plastic packaging materials;

[0083] S43, rinse the device with isopropyl alcohol to remove the deionized water remaining on the surface of the device and keep the surface of the device dry.

[0084] S5, using scanning electron microscope SEM to determine the reliability of Cu lead and Cu lead / Al pad after electrolytic corrosion:

[0085] S51, after the electrolytic corrosion is completed, the device after desealing and drying is observed using a scanning electron microscope (SEM) to determine whether the ball bonding and wedge bonding are completely visible, and the Cu lead diameter is measured and compared with the product manual;

[0086] S52, when the reliability of Cu lead and Cu lead / Al pad is good, remove the anti-static tape covering the area outside the window slot of the plastic package device.

[0087] The contents not described in detail in this specification belong to the prior art known to those skilled in the art. It is obvious to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, no matter from which point of view, the embodiments should be regarded as exemplary and non-restrictive, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims are included in the present invention.

Claims

1. A method for unsealing a commercial plastic-sealed device containing Cu leads, characterized in that: The method is specifically as follows: S1, using X-ray to determine the highest point of the Cu lead and the distribution area of ​​the bonding points of the plastic packaged device; S2, using laser ablation to groove the positioning window area of ​​the plastic packaging material on the upper surface of the device, and combining X-ray to control the thickness of the plastic packaging material above the highest point of the Cu lead within an appropriate range; S3, using a mixture of fuming nitric acid and concentrated sulfuric acid to electrolytically corrode the plastic sealing material at the bottom of the slotted window area, decompose the epoxy resin, and retain the ceramic filler; S4, using acetone to dissolve the residual fuming nitric acid and concentrated sulfuric acid mixture; using deionized water to remove the ceramic filler; using isopropyl alcohol to keep the device dry; S5, using scanning electron microscope (SEM) to determine the reliability of Cu lead and Cu lead / Al pad after electrolytic corrosion.

2. The method for unsealing a commercial plastic-sealed device containing Cu leads according to claim 1, characterized in that: The method of using X-rays to determine the highest point of the Cu lead of the plastic-encapsulated device in step S1 is to determine the device pad plating material, Cu lead size, and device plastic encapsulation material thickness based on the product manual, and to observe the device from the front using X-rays to determine the highest point of the Cu lead of the device.

3. The method for unsealing a commercial plastic-sealed device containing Cu leads according to claim 1, characterized in that: The bonding point distribution area of ​​the plastic-encapsulated component is determined in step S1 by observing the component from the top surface using X-rays to determine the bonding point distribution area of ​​the component.

4. The method for unsealing a commercial plastic-sealed device containing Cu leads according to claim 1, characterized in that: The method of using laser ablation to groove the positioning window area of ​​the plastic packaging material on the upper surface of the device in step S2 is as follows: A1. Use solder to short-circuit all external pins of the plastic-encapsulated device to provide circuit bias conditions for the device; A2. Determine the optimal size and shape area for laser etching based on the highest point of the Cu lead and the distribution area of ​​the bonding points observed by X-ray, and use it as the plastic sealing slot window area; A3. Use a positioning tool of a laser etching machine to mark the plastic sealing slot window area, and limit the area for subsequent plastic sealing opening to the slot window area.

5. The method for unsealing a commercial plastic-sealed component containing Cu leads according to claim 1, characterized in that: The step S2 of controlling the thickness of the plastic encapsulation material above the highest point of the Cu lead within an appropriate range by combining X-rays is to further observe the plastic encapsulation device after laser etching from the front through X-rays to ensure that the distance between the lowest point of the window area after laser etching and the highest point of the Cu lead is less than or equal to 1 mm.

6. The method for unsealing a commercial plastic-sealed device containing Cu leads according to claim 1, characterized in that: In step S3, the plastic sealing material at the bottom of the slotted window area is electrolytically corroded by using a mixture of fuming nitric acid and concentrated sulfuric acid to decompose the epoxy resin and retain the ceramic filler. The specific method is as follows: B1, using antistatic tape that does not react with the fuming nitric acid and concentrated sulfuric acid mixture to cover the area outside the slot, 90-98% fuming nitric acid HNO3 and 90-98% concentrated sulfuric acid H2SO4 are mixed in a mass ratio of 4:1-2:1 to form the fuming nitric acid and concentrated sulfuric acid mixture, and the temperature of the fuming nitric acid and concentrated sulfuric acid mixture is maintained at 50-80°C to generate NO2 + Ions and HSO4 - ion; B2. Connect the short-circuited external pin of the device to the positive pole of the power supply. When the power is on, hydrogen H2 is formed on the surface of the metal sheet corresponding to the negative pole of the power supply. - The ions begin to electrolytically corrode the epoxy resin in the plastic packaging material, and the plastic packaging device connected to the positive electrode of the power supply and the negative electrode metal sheet are immersed in the fuming nitric acid and concentrated sulfuric acid mixture at the same time. + The ions continuously decompose the epoxy resin; the remaining main parts of SiO2, Al2O3, and AlN ceramic fillers in the plastic packaging material float in the mixed liquid and adhere to the chip surface, pad surface, and wire bonding; HSO4 - The ions are adsorbed on the Cu lead; B3. Maintain the power supply voltage of the electrolytic corrosion at 16 V, and take out the plastic-encapsulated device from the fuming nitric acid and concentrated sulfuric acid mixture every 30 seconds; check the electrolytic corrosion degree of the epoxy resin and the visibility of the Cu wire bonding by a low-power optical microscope. When the Cu wire bonding is clearly visible, use a high-power optical microscope to preliminarily measure the Cu lead diameter and the potential pit area on the Cu lead surface.

7. The method for unsealing a commercial plastic-sealed device containing Cu leads according to claim 1, characterized in that: In step S4, acetone is used to dissolve the residual fuming nitric acid and concentrated sulfuric acid mixture, and the specific method is as follows: The device is rinsed with acetone to dissolve and remove the residual fuming nitric acid and concentrated sulfuric acid mixture on the surface of the device.

8. The method for unsealing a commercial plastic-sealed device containing Cu leads according to claim 1, characterized in that: In step S4, deionized water is used to remove the ceramic filler, and the specific method is as follows: Gently spray deionized water on the surface of the Cu lead to remove HSO4 on the surface of the Cu lead. - Ion protective coating, as well as SiO2, Al2O3, and AlN ceramic fillers remaining after reaction in the plastic packaging material.

9. The method for unsealing a commercial plastic-sealed device containing Cu leads according to claim 1, characterized in that: The specific method of using isopropyl alcohol to keep the device dry in step S4 is as follows: Rinse the device with isopropyl alcohol to remove any residual deionized water on the device surface and keep the device surface dry.

10. The method for unsealing a commercial plastic-sealed component containing Cu leads according to claim 1, characterized in that: The SEM scanning electron microscope is used in step S4 to determine the reliability of the Cu lead and the Cu lead / Al pad after electrolytic corrosion. The specific method is as follows: After the electrolytic corrosion is completed, the SEM scanning electron microscope is used to further observe the device after unsealing and drying to determine whether the ball bonding and wedge bonding are completely visible, measure the diameter of the Cu lead, and compare it with the product manual; when the reliability of the Cu lead and Cu lead / Al pad is good, remove the anti-static tape covering the area outside the window slot of the plastic-encapsulated device.